Conflictos de usos del suelo como aporte a la sostenibilidad agroproductiva del bosque Politécnico de la ESPAM MFL - Cárdenas Astudillo, Angela Juliana (2024)
The objective of the research was to diagnose the existing land use conflicts at Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, as a contribution to the agro-productive sustainability of the place, relating the coverage and current use of the land with its capacity of uses, in addition, geographic information systems were used to prepare maps for each phase. To determine the coverage and current use of the land, direct observation and obtaining aerial images were used using the DJI Phantom 4 Pro drone, with regard to the capacity of land uses, physical and chemical analyzes were carried out based on the CLIRSEN methodology and the USDA – LCC system, taking into account the following variables: texture, pH, salinity, stoniness, drainage, slope and climate and for the conflicts, the coverage and current use of the soil was related to its capacity for uses, the research showed that the Polytechnic Forest is divided into 4 uses, where forest use predominates with 64,27% of the area, followed by other uses (bare soil, infrastructure and body of water) representing 17,54%, with a smaller proportion of the area of conservation and/or protection 12,63% and the agricultural area with 5,56%, in the soil capacity it was obtained that 78,98% of the soils are class II and 21,02% are class I, thus diagnosing that 4,71% of the land in the Polytechnic Forest are lands without conflicts of use and the remaining 95,29% are lands with conflicts due to underutilization, being a value higher than the idea to be defended, which was 15% due to underutilization.